Towards an integrated model for supervision for mental health and psychosocial support in humanitarian emergencies: A qualitative study. - Camila Perera (Public Library of Science (PLoS), 2021)
Background Despite recent advances in the development and provision of mental health and psychosocial support (MHPSS) in humanitarian settings, inadequate supervision remains a significant barrier to successful implementation. The present study sought to incorporate broad stakeholder engagement as part of the first phase of development of a new Integrated Model for Supervision (IMS) for use within MHPSS and protection services in humanitarian emergencies. Methods Semi-structured interviews were conducted with 26 global mental health professionals. Data was analysed thematically, using a combination of inductive and deductive methods. Codes and themes were validated through co-author cross-checks and through a webinar with an expert advisory group. Results Results reinforce the importance of effective supervision to enhance the quality of interventions and to protect supervisees' wellbeing. Participants generally agreed that regular, supportive supervision on a one-to-one basis and as a separate system from line management, is the ideal format. The interviews highlight a need for guidance in specific areas, such as monitoring and evaluation, and navigating power imbalances in the supervisory relationship. Several approaches to supervision were described, including some solutions for use in low-resource situations, such as group, peer-to-peer or remote supervision. Conclusion An integrated model for supervision (IMS) should offer a unified framework encompassing a definition of supervision, consolidation of best practice, and goals and guidance for the supervisory process.